POLA PERMUKIMAN MANDALANGEN DI SEKITAR KERATON KASEPUHAN CIREBON - Ari Widyati Purwantiasning (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2011)
This research is aimed to explore the Mandalangen settlement pattern which laid surround Kasepuhan Cirebon Palace, related to Ching and Kevin Lynch theories. Used descriptive qualitatative method, the study done by comparing the sketches of Mandalangen settlement with those theories. The research results several facts that there are relationships between the theories and Mandalangen settlement pattern. Beside that,it is found that the streets become more narrow and housing area extended cause by increasing of human need.Those results is very important to arrange conservation programme at the Mandalangen settlement.